2012
DOI: 10.5152/akd.2013.004
|View full text |Cite
|
Sign up to set email alerts
|

Expert panel on cost analysis of atrial fibrillation

Abstract: Objective: To estimate total cost of atrial fibrillation (AF) management concerning acute coronary syndrome, heart failure, stroke and drug related adverse events with respect to clinical practice and available guidelines.Methods: This cost analysis study was based on identification of total costs related to management of acute coronary syndrome, heart failure, stroke and the drug related adverse events in patients with AF based on standardized questionnaire forms filled by experts according to their daily cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…They calculated the daily cost of HF patients as 258 TL and the total cost per admission as 2351 TL (14). These findings were very similar to a recent data based on expert panel views conducted in Turkey by Fak et al (15), where cost for HF was reported as 2435 TL per patient. When all these observations are taken into account, an up-to-date documentation of the cost of HF management considering both in-patient and out-patient source utilization in Turkey may help to demonstrate the economic burden of HF in actual clinical practice in Turkey.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…They calculated the daily cost of HF patients as 258 TL and the total cost per admission as 2351 TL (14). These findings were very similar to a recent data based on expert panel views conducted in Turkey by Fak et al (15), where cost for HF was reported as 2435 TL per patient. When all these observations are taken into account, an up-to-date documentation of the cost of HF management considering both in-patient and out-patient source utilization in Turkey may help to demonstrate the economic burden of HF in actual clinical practice in Turkey.…”
Section: Introductionsupporting
confidence: 92%
“…A cost analysis study by Fak et al (15) was based on identification of total costs related to management of acute coronary syndrome, HF, stroke, and the drug related adverse events in patients with atrial fibrillation, the average total cost of HF was reported as 4,524 TL (2,436 TL within the first month and 2,088 TL within a year excluding the first month) according to experts’ view. In our analysis, the total annual cost of HF management was found to be 1,537 TL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other countries, earlier studies have determined the treatment costs of CVDs, but they did not compare patient subgroups and included only a limited number of determinants for costs (10, 11). Therefore, this study aimed to determine the degree of association of costs for acute myocardial infarction, heart failure, and angina pectoris in a university hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…This identified 261 records, of which eight papers [99][100][101][102][103][104][105][106] not previously identified were considered relevant after title and abstract screening and a further four papers [107][108][109][110] were highlighted as providing information on costs.…”
Section: Outcomes Of the Economic Evaluationmentioning
confidence: 99%